Quantitative Analysis of Regional Luxury Brand Marketing Using Logit Model - Xianfeng Chen (Journal of Mathematics)
The luxury consumer market in my country is developing rapidly. However, due to the differences in the culture and consumer psychology of different regions in my country, the marketing status of luxury goods in my country will be different in different regions. Under the premise of analyzing consumer groups, it deeply analyzes the factors that affect the luxury consumption psychology of Chinese consumers, expounds this psychological state, and then analyzes the problems existing in my country’s luxury goods marketing. Finally, based on consumer psychology, suggestions on luxury marketing related to these issues have been put forward. In addition, quantitative research on marketing and how to psychologically open a new chapter of marketing in the luxury goods industry have always been the core themes that foreign marketing researchers will continue to explore for a long time. The logo model is an excellent analysis in this process. By introducing the principles of the logo model and applying this model to the empirical study of domestic consumers’ choice of a specific luxury brand, it is shown that the logo model can be used to analyze many problems in marketing research. More useful quantitative information is undoubtedly of great benefit to the academic research of marketing and the practice of marketing management.